Exploration of Shariah Non-Compliant Risk: Evidence from Indonesia - Ma'ruf, Aminudin; Wulandari, Asih Putri (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2023)
Sharia non-compliance is a peculiar risk that Islamic financial institutions must face. This study aims to explore and analyse the presence of Sharia non-compliant risk in Indonesia. The method used in this study is a descriptive normative legal research method with a qualitative approach, using related literature books and journals. The study's data was obtained from religious courts in Indonesia and Sharia committee data from the annual reports of Indonesian Islamic banks. The study results concluded that some Sharia non-compliance risk cases in Indonesia need serious attention from the Islamic financial industry. The Sharia non-compliance cases are dominated by default in Shariah. Therefore, the study urges maximization of the role of the Sharia committee and the development of the nation's literacy of Islamic economics and finance. The study comes with recommendations for policymakers and carries some limitations for future studies in Shariah non-compliant risk.